Interactive Effects of Foliar-Applied Nano NPK and Humic Acid on Growth and Yield of Broccoli (Brassica oleracea var. italica) - Abdulrahman, Nigar; Niyan Jalal Qadir; Hawar Ali Maruf; Sazan Fathi Sharif (University of Thi-Qar Journal of agricultural research, 2025)
In field conditions, the effect of nano NPK fertilizers and humic acid treatments as foliar spray on growth, yield, and nutrient content of broccoli (Brassica oleracea var. italica) in a greenhouse was applied. A field experiment was conducted (2022-2023 seasons) under greenhouse conditions at Bakrajo Technical Institute of Sulaimani by using RCBD with synthetic nano as fertilizer at (0, 2.0 ml, 4.0 ml, and 6.0 ml L-1 and humic acid at 0, 2.5, 4.5, and 6.5 ml L-1 and drawing on two weeks, then repeating them after a space of two weeks for six weeks. Plants were analyzed for a range of traits such as plant size, root and stem growth, chlorophyll levels, yield, and mineral content. The results showed that while both treatments improved broccoli performance, humic acid consistently had the strongest impact. Plants treated with humic acid—especially at 2.5 to 6.5 mL/L—produced larger leaves, thicker stems, greater root weight, and higher head yield. The highest yield ever witnessed has been 7.54 tons per hectare under 2.5 mL/L humic acid treatment. There are also significantly higher levels of chlorophyll content and uptake of essential nutrients such as nitrogen, phosphorus, potassium, and iron in these treatments. Nanoparticulate NPK induced improvements, mostly with chlorophyll content and nutrient content, but its effects were mostly overshadowed by humic acid. All in all, this implies the application of humic acid with or without nano NPK in the production of broccoli goes well environmentally and supports the growth and quality of broccoli. This thesis strengthens the claim that combining organic biostimulants with modern nutrient delivery methods could help farmers gain better yields while cutting down on the use of standard chemical fertilizers. A path of sustainable development in present-day horticulture.